Інтегральні сенсори магнітого поля - Вітюк, Д. В. (ХНУРЕ, 2025)
High-precision sensors are increasingly in demand among developers in many industries, such as automotive, robotics, aerospace, and healthcare. Accurate measurements are important for safety and efficiency, especially in applications like electric vehicles, where accurate current sensing is vital for battery and motor control, medicine, and home appliances.
Keywords: інтегральний сенсор; High-precision sensors